2020
DOI: 10.14814/phy2.14407
|View full text |Cite
|
Sign up to set email alerts
|

Adverse maternal environment and western diet impairs cognitive function and alters hippocampal glucocorticoid receptor promoter methylation in male mice

Abstract: Adverse maternal environment (AME) and high-fat diet in early childhood increase the risk of cognitive impairment and depression later in life. Cognitive impairment associates with hippocampal dysfunction. A key regulator of hippocampal function is the glucocorticoid receptor. Increased hippocampal GR expression associates with cognitive impairment and depression. Transcriptional control of GR relies in part upon the DNA methylation status at multiple alternative initiation sites that are tissue specific, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…All experiments were conducted according to the Public Health Services Policy on Human Care and Use of Laboratory Animals and all procedures were approved by the Medical College of Wisconsin Institutional Animal Care and Use Committee [40]. The mouse model of AME used in this study has been previously described [41]. Briefly, AME was induced in mice by exposing sixweek-old C57/Bl6 female mice randomly to either a control diet (10% fat without cholesterol and sucrose, Research Diet Inc., New Brunswick, NJ, USA, Product# D14020502) or a WD (40% fat, composed of increased saturated fat, cholesterol, and sucrose, Research Diet Inc., Product# D12079B) for 5 weeks prior to pregnancy and throughout lactation.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…All experiments were conducted according to the Public Health Services Policy on Human Care and Use of Laboratory Animals and all procedures were approved by the Medical College of Wisconsin Institutional Animal Care and Use Committee [40]. The mouse model of AME used in this study has been previously described [41]. Briefly, AME was induced in mice by exposing sixweek-old C57/Bl6 female mice randomly to either a control diet (10% fat without cholesterol and sucrose, Research Diet Inc., New Brunswick, NJ, USA, Product# D14020502) or a WD (40% fat, composed of increased saturated fat, cholesterol, and sucrose, Research Diet Inc., Product# D12079B) for 5 weeks prior to pregnancy and throughout lactation.…”
Section: Animalsmentioning
confidence: 99%
“…Like a protein-coding gene, miR expression can be epigenetically regulated [31][32][33]. Additionally, measurable epigenetic changes often occur in effected genes following an adverse early life environment [41]. We then determined the effect of AME on DNA methylation status and histone code at miR-10b promoter.…”
Section: Ame Altered Epigenetic Characteristics At Mir-10b Promoter In the Hippocampusmentioning
confidence: 99%
See 1 more Smart Citation
“…Human studies have examined how WD impairs hippocampal function and ingestive behavior (Stevenson et al, 2020). Several animal studies have been performed using memory tasks showing that WD consumption impairs hippocampal-dependent memory tasks (Francis and Stevenson, 2013;Ke et al, 2020). For example, a recent meta-analysis included 41 studies in which different tasks to assess hippocampal-dependent spatial learning and memory were carried out, and they showed that high-fat and -sugar diets may impair hippocampal-dependent forms of cognition (Abbott et al, 2019).…”
Section: Wd and Behaviormentioning
confidence: 99%
“…Epigenetic changes are most visible in the glucocorticoid receptor (GR) gene promoter and subsequent GR signalling in the central tissues of the GC feedback loop (Koss and Gunnar, 2018). Differential methylation of the GR has been associated with adverse maternal environment (Stonawski et al, 2019), diet (Ke et al, 2020), early life stress (Holmes, 2019), exposure to environmental toxins (Meakin et al, 2019), chronic stress (Rowson et al, 2019) and institutionalisation (Elwenspoek et al, 2019) among other sources. Epigenetic modification of the GR and related genes presents the best biomarker of ELA up to date, but these methylation changes might only occur in brain regions, making them inaccessible for preventive medicine (Lewis et al, 2020), since the peripheral GR does not appear to be functionally or transcriptionally altered (Elwenspoek et al, 2019).…”
Section: Biological Components and Consequences Of Elamentioning
confidence: 99%